Sakramen Baptis Dalam Perspektif Hukum Kanonik Gereja dan Pastoral: Studi Kasus Atas Tanggung Jawab Pelayan Sakramen - Yanto Sandy Tjang; Mayong Andreas Acin (Sekolah Tinggi Katolik Touye Paapaa Deiyai, 2025)
The sacrament of baptism holds a highly fundamental position in the life of the Catholic Church, as it constitutes the foundation of Christian life and the gateway to the reception of other sacraments. This article examines the responsibilities of ministers of baptism from canonical and pastoral perspectives, focusing on three main issues: the recording of baptism for adopted children, the handling of lost baptismal records, and the eligibility of religious men and women to serve as godparents. The study employs a qualitative approach using a normative-theological method through a literature review of the Codex Iuris Canonici, the Catechism of the Catholic Church, various pastoral documents, and relevant academic literature. The findings indicate that the administration of baptism must be carried out validly, accurately, and with compassion, balancing administrative legal precision with pastoral sensitivity. In the baptism of adopted children, record-keeping must comply with both ecclesiastical law and civil documentation while safeguarding the child’s dignity and privacy. In cases of missing baptismal records, pastors are obliged to conduct proper canonical verification and, if necessary, perform conditional baptism to ensure legal certainty and spiritual welfare. Meanwhile, religious brothers and sisters may serve as godparents if they meet canonical requirements and possess the genuine capacity to accompany the baptized child’s growth in faith. This study affirms that every ecclesial act must be grounded in the principle salus animarum suprema lex—that the salvation of souls is the supreme law—so that the administration of baptism embodies an integral harmony between juridical order, pastoral care, and the saving love of Christ.